Depletion of melamine and cyanuric acid in kidney of catfish Ictalurus punctatus and trout Oncorhynchus mykiss. Issue 6 (17th May 2013) - Stine, C. B.; Nochetto, C.; Gieseker, C. M.; Evans, E. R.; Hasbrouck, N. R.; Mayer, T. D.; Girard, L.; Reimschuessel, R.
Abstract : A risk assessment conducted in 2007 identified significant knowledge gaps about tissue residues of melamine and related triazine analogs such as cyanuric acid in animals that had eaten contaminated food. The USFDA subsequently designed studies to determine residue levels in muscle, serum, and kidneys of catfish and trout given a single gavage dose of 20 mg/kg body weight (BW) of melamine, cyanuric acid, or 20 mg/kg BW of both compounds simultaneously. Renal triazines were determined by LC‐MS/MS at postdose days 1, 3, 7, 14, 28 (and day 42 for trout). When dosed individually, melamine and cyanuric acid kidney residues depleted much faster than those in fish given both compounds together. Combined dose residue depletion was punctuated by extreme outliers due to the formation of persistent renal melamine cyanurate crystals.